Protective effect of olive leaf (Olea europaea L.) extract against chronic exposure of liver and kidney tissues of Wistar rats to aluminum chloride - Ahila Meliana; Arifian Hardi Putri Ratnani; Nurina Hasanatuludhhiyah; Alphania Rahniayu; Gondo Mastutik; Anny Setijo Rahaju (Shahrekord University of Medical Sciences, 2024)
Introduction: The liver and kidney are the main sites of aluminum (Al) accumulation. Lifetime exposure to significant amounts of Al is inevitable, hence its toxicity on the liver and kidney should be a health concern. Natural antioxidants have been proven to alleviate pathologies in various liver and kidney injuries. However, the effect of olive leaf extract (OLE) on Al-exposed animals is yet to be confirmed. This study aimed to investigate the OLE effect against AlCl3 chronic exposure in rats' liver and kidneys. Methods:Thirty-two male Wistar rats were divided into four groups (n=8), including the control group, the AlCl3 group treated with 128 mg/kg AlCl3 solution, as well as AlCl3 +OLE50, and AlCl3 +OLE100 groups (Other than AlCl3 they received 50 and 100 mg/kg of OLE, respectively, 2 hours after AlCl3 administration). All treatments were given orally for 12 weeks. All groups were evaluated for liver and kidney histopathological features, then scoring was performed. Results: AlCl3 administrations produced histopathological lesions in the liver and kidney, indicated by increased liver necro-inflammatory grades, ballooning scores, and renal inflammatory cell infiltration (P<0.05). OLE100 mg/kg significantly reduced liver necroinflammatory grade, ballooning score, and kidney inflammatory cell infiltrations. The dose of 50 mg/kg also reduced these parameters (P<0.05), except for the liver necro-inflammatory grade. There was a significant correlation between OLE dose and liver necro-inflammatory grade and ballooning score amelioration. Conclusion: OLE ameliorates liver and kidney histopathological features induced by oral Al chronic exposure in a dose-dependent manner.